The possible role of interleukin-33 as a new player in the pathogenesis of contrast-induced nephropathy in diabetic rats. (2nd July 2016) - Demirtas, Levent; Turkmen, Kultigin; Kandemir, Fatih Mehmet; Ozkaraca, Mustafa; Kucukler, Sefa; Gürbüzel, Mehmet; Comaklı, Selim
Abstract: Introduction : Patients with diabetic kidney disease (DKD) are more prone to contrast-induced nephropathy (CN). Apoptosis and autophagy were found to be essential in the pathogenesis of DKD. Interleukin-33 (IL-33) is a cytokine, but its role in DKD and CN is unknown. As IL-33 is modulated by apoptosis, we aimed to determine the relationship between IL-33 apoptosis and autophagy in DKD with CN.Materials and methods : Thirty male Sprague–Dawley rats were enrolled and randomly allocated into three groups. The first group was comprised of healthy rats (HRs), whereas the other two groups were made up of diabetic rats (DRs) and diabetic rats with CN (DRs + CN). All groups except the HRs received 50 mg/kg/day of streptozotocin (STZ). The DRs + CN group was induced by administering 1.5 mg/kg of intravenous radiocontrast dye on the 35th day.Results : We observed increased IL-33 in the kidney tissue following induction of CN in the DRs. The DRs showed moderate immunopositivity, and the DRs + CN showed severe immunopositivity for caspase-3, cleaved caspase-3, caspase-8, caspase-9, LC3B, and Beclin-1 in tubular cells and glomeruli. The DRs also showed moderate immunopositivity in tubular cells, and the DRs + CN group showed severe immunopositivity for IL-33 in tubular cells. Increased caspase-3 was found in both glomeruli and tubuli; however, we could not demonstrate IL-33 in glomeruli. This could be secondary to inactivation of IL-33 via increased caspase-3 activity.Conclusion : The release of IL-33 from necrotic cells might induce autophagy, which can further balance the effects of increased apoptosis secondary to CN in DKD.